RHODIUM AND OTHER PLATINUM-GROUP ELEMENTS IN CARBONACEOUS CHONDRITES - Jochum K.P. (My University, 1996)
Five carbonaceous chondrites (including the CI chondrites Orgueil and Ivuna) were analyzed by spark source mass spectrometry (SSMS) for the platinum-group elements Ru, Rh, Os, Ir, Pt, as well as W, Re, Au, Th, and U. Conventional photoplate detection and a recently developed multi-ion counting system were used for ion detection. Results obtained for CI chondrites agree with compiled values within 6%. This study contains the first Rh analyses for this chondrite group. Rhodium concentrations for Orgueil and Ivuna agree well, implying a Solar System abundance of 0.140 +/- 0.004 ppm and corresponding to 0.359 +/- 0.010 atoms relative to 1 ? 106 Si atoms. Concentrations in CM2, CV3, and CK4 chondrites are enriched compared to those of CI chondrites. However, the abundances of the refractory siderophile elements Re, Os, Ir with condensation temperatures above 1600 K (at 10?4 atm) are higher by about 15-20% compared to the less refractory elements Ru, Pt, and Rh. Elements with similar condensation temperatures correlate very well resulting in uniform concentration ratios of Rh/Pt = 0.136 +/- 0.006, Re/Os = 0.0821 +/- 0.0019, and Ir/Os = 0.949 +/- 0.039.